The relationships of environmental factors and customer-focus manufacturing strategy insights from Taiwan's Textile Industry. - Tseng, Ming-Lang (Philippine Industrial Engineering Journal)
Recent studies have pointed out the important role of the business environment on the manufacturing strategy choices by organizations. The literatures have generally argued that the changed manufacturing environment requires is the adoption of customer-focused manufacturing strategy. This research extends the researches on selected business environment and customer focus manufacturing strategy by presenting results from textile industry. Using data collected from textile manufacturing firms in the Taiwan. We are exploring the link of business environment factors and customer-focus manufacturing strategy. We demonstrate through descriptive and regression methods. Implications and conclusions are discussed.